Accessing Medical Information on Smart-Phone: Usage and Perception among Post Graduate Students of A Medical College, Central Karnataka - A Cross Sectional Study - Aswin Kumar; G K Ratnaprabha; Faye Rose Anatao (Medsci Publications, 2020)
Introduction: There is scant reliable evidence on the usage of smart phone by postgraduate students/residents in India. The study conducted to assess the usage of smart phone to access medical information among postgraduate students of a medical college and to explore the perceptions about accessing medical information on smart phone among them. Methodology: A cross sectional study was done among postgraduate students of a medical college in central Karnataka during December 2018 to January 2019. Every postgraduate student of the college available at the campus was approached for the study. Results: Smart-phone use and internet facility in it was almost universal (99.2%). Mean years of smart-phone usage among postgraduates was 7.4 + 2.5 years and they were using internet around 3.4 + 1.5 hours a day. Medical information was accessed by 97.4% of postgraduates over smart-phone and pubmed was the most common site accessed. Information on drug dosages and search for seminar presentations were the most searched reasons. Usefulness of medical information available on internet was graded at 3.62 + 0.85 on a scale of 0-5. Conclusions: Online information aid clinical/academic activity of the subjects significantly. This makes it necessary to train them about the search methodologies and information about validity and reliability of the information provided in the online resources.